International Students’ Motivation and Learning Approach: A Comparison with Local Students - Chue, Kah Loong; Nie, Youyan (Journal of International Students, 2016)
Psychological factors contribute to motivation and learning for international students as much as teaching strategies. 254 international students and 144 local students enrolled in a private education institute were surveyed regarding their perception of psychological needs support, their motivation and learning approach. The results from this study indicated that international students had a higher level of self-determined motivation and used a deep and surface learning approach more extensively than local students. Perceived psychological needs support positively predicted intrinsic motivation, identified regulation and a deep learning approach for both groups. There were also differences in the effects of motivation on learning approach between the two groups. Further possibilities for exploration are discussed in this study.